2013
DOI: 10.1002/bjs.9059
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic regeneration and functional recovery following partial liver resection in an experimental model of hepatic steatosis treated with omega-3 fatty acids

Abstract: Omega-3 FAs effectively reduced severe hepatic steatosis, which was associated with improved liver regeneration and functional recovery following partial hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 28 publications
3
44
1
1
Order By: Relevance
“…One study investigating this issue on a regenerating liver found a reduction in ROS production and an improvement in the antioxidant system [6]. Another study dealing with Ω3FAs supplementation, which did not use a regeneration model, reported that this compound did protect against oxidative stress induced DNA-damage in the liver [7]. However, there are contradicting studies reporting negative effects of long chain Ω3FAs on regenerating [26] and normal liver [27] with diverse results on oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study investigating this issue on a regenerating liver found a reduction in ROS production and an improvement in the antioxidant system [6]. Another study dealing with Ω3FAs supplementation, which did not use a regeneration model, reported that this compound did protect against oxidative stress induced DNA-damage in the liver [7]. However, there are contradicting studies reporting negative effects of long chain Ω3FAs on regenerating [26] and normal liver [27] with diverse results on oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 fatty acids (Ω3FAs) and their longer chain downstream products such as eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA) and docosahexaenoic acid (DHA) have been demonstrated as beneficial on the liver in several different aspects [456]. However, the number of studies focusing on the effects of Ω3FAs on liver regeneration is relatively few with different results [78]. Moreover, the effects of adding these emulsions to total parenteral nutrition (TPN) on the oxidative stress, which develop in the regenerating liver, are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Marine-derived food sources such as fatty fish, seaweed, shellfish, microalgae and krill are rich in u-3 [13,14]. u-3 supplements are reported to be used in hepatic injury and steatosis [15]. EPA and DHA protected against arachidonic acid produced pro-inflammatory molecules through conversion to less inflammatory mediators, so EPA and DHA have antiinflammatory effects [16].…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, V3FA seem to improve recovery of lean liver from resection-induced liver failure, or of fatty liver after standard resection. 14,15 Whether such effects are indirect (eg, by protecting from injury) or direct (eg, by promoting hepatocyte proliferation) remains unclear, but the resulting benefits can also be observed in the clinic. 16 Finally, V3FA have been associated with anti-cancerous properties in a variety of neoplasms.…”
mentioning
confidence: 99%